O programa NAS/CNPq: avaliação de um participante - Brocksom,Timothy John (2007)
The NAS/CNPq programme in Chemistry ran from 1969 to 1974, and brought recent PhD and post-doctoral chemists to the Chemistry Institutes at the University of São Paulo and the Federal University of Rio de Janeiro. The purpose was to create and direct new research topics in selected areas of chemistry, and participate in the post-graduate programmes. As a participant in this programme, I present my personal views, some background information, and an evaluation of this programme for the advance of synthetic organic chemistry in Brazil.